Life assessment of marine ethylene propylene rubber power cables based on hardness retention rate - Meng Xiaokai; Wang Zhiqiang; Li Guofeng (Archives of Electrical Engineering, 2017)
The lifetime of ethylene propylene rubber (EPR) insulated cables will decrease because of complex aging processes. From the safety perspective, insulation condition assessment of the cable is essential to maintain an efficient and reliable operation. As a nondestructive and online evaluation method, a hardness retention rate was used to estimate the lifetime of cable. First, accelerated thermal aging tests in the laboratory were performed to measure the elongation at break retention rate (EAB%) and a hardness retention rate at different temperatures. Second, the aging values were processed by the Arrhenius equation and time temperature superposition to assess aging lifetime of insulation at different temperatures and end levels. As the insulation condition assessment of the cable by hardness retention test has no approved standard, the EAB% data were correlated with hardness retention to provide an evaluation basis. The results show that when EAB% picks out the time corresponding to a certain amount of 50% degradation, 10% of hardness retention was chosen as the termination index.